Mechanics of Work-related Back Pain: An Analytical Review - Alsufyani, Omar S.; AlSufyani, Renad S.; Altowairqi, Abdulrahman E; AlTowairqi, Tethkar M.; Altowairqi, Mohammed H. (International Journal of Innovative Research in Medical Science, 2021)
The prevalence of Low back pain (LBP) is exceedingly high, upwards of 80% in the general population. LBP is manifested as pain in the thoraco-lumbar area and often related to a muscle pull. This paper is a narrative review of the mechanics of work-related low back pain. In this paper, the researchers provide a different insight of the occupational low back pain as they introduce a theoretical background of the occupational low back pain and management of low back pain at workplace. In addition, the study highlight the research focus within the field of mechanical loading and biomechanical assessment methods of low back pain. The study found that low back pain is a reversible process in case causes are identified. However, it is a challenging issue to identify the causes unless well-designed models and assessment methods are applied for each case separately.